Impurity induced non-bulk stacking in chemically exfoliated h-BN nanosheets - NICOLOSI, VALERIA (My University, 2013)
Structural characterization of 2D nanomaterials is an important step towards their future applications. In this work we carried out imaging and structural analysis of 2D h-BN produced by chemical-exfoliation, emphasizing the stacking order in few-layer sheets. Our analysis, for the first time has shown conclusively that non-bulk stacking can exist in 2D h-BN.
PUBLISHED
Keywords: Nanomaterials